Oxidative potential and persistent free radicals in dust storm particles and their associations with hospitalization - Linjun Qin; Lili Yang; Ling Liu; Shilu Tong; Qian Liu; Gang Li; Haiyan Zhang; WuYuxin Zhu; Guorui Liu; Minghui Zheng; Guibin Jiang (Nature Communications)
Abstract Sand and dust storms (SDS) can cause adverse health effects, with the oxidative potential (OP) and environmentally persistent free radicals (EPFRs) inducing oxidative stress. We mapped the OP and EPFRs concentrations at 1735 sites in China during SDS periods using experimental data for 2021–2023 and a random forest model. We examined 855,869 hospitalizations during SDS events for 2015–2022 in Beijing, China. An integrated exposure–response model was used to estimate the association between OP and EPFRs and hospitalization during SDS. EPFRs were strongly associated with circulatory (3.05%; 95% confidence interval [CI]: 1.01%, 4.08%) and respiratory (2.02%; 95% CI: 1.01%, 4.08%) diseases with each increase of 1012 spins/m3. The OP effects on circulatory (3.52%; 95% CI: 2.13%, 4.92%) and respiratory diseases (2.08%; 95% CI: 1.13%, 3.04%) with each increase of 0.2 nmol/min/m3 were also statistically significant. Additionally, 20.47% and 27.26% of all-cause hospitalizations were attributable to OP and EPFRs exposure, respectively. This knowledge could be used to develop effective sand and dust risk prevention in dust-prone countries.